Strategi Umat Islam Menghadapi Tantangan Kontemporer: Pasca Clash of Civilizations dan Islamophobia - Gina Aulia Fadilla; Tenny Sudjatnika (Indo Publishing, 2025)
This article explores how Muslims develop strategies to address contemporary global challenges, particularly in response to Samuel P. Huntington’s Clash of Civilizations theory and the growing phenomenon of Islamophobia. Using a descriptive qualitative approach based on literature review, this study examines several efforts undertaken by the Muslim community, such as prioritizing peaceful preaching, promoting an inclusive educational system that embraces diversity, and strengthening Muslim participation in the political sphere to build a positive image. Furthermore, global initiatives like the Makkah Declaration and the Amman Message play a significant role in supporting these efforts. Indonesia is presented as a concrete example, where moderate Islamic practices and openness to interfaith dialogue have successfully fostered social harmony and helped reduce negative perceptions of Islam.